Consensus guidelines on perioperative management of malignant hyperthermia suspected or susceptible patients from the European Malignant Hyperthermia Group. (January 2021) - Rüffert, Henrik; Bastian, Börge; Bendixen, Diana; Girard, Thierry; Heiderich, Sebastian; Hellblom, Anna; Hopkins, Philip M.; Johannsen, Stephan; Snoeck, Marc M.; Urwyler, Albert; Glahn, Klaus P.E.; ,; et al.
Summary: Malignant hyperthermia is a potentially fatal condition, in which genetically predisposed individuals develop a hypermetabolic reaction to potent inhalation anaesthetics or succinylcholine. Because of the rarity of malignant hyperthermia and ethical limitations, there is no evidence from interventional trials to inform the optimal perioperative management of patients known or suspected with malignant hyperthermia who present for surgery. Furthermore, as the concentrations of residual volatile anaesthetics that might trigger a malignant hyperthermia crisis are unknown and manufacturers' instructions differ considerably, there are uncertainties about how individual anaesthetic machines or workstations need to be prepared to avoid inadvertent exposure of susceptible patients to trigger anaesthetic drugs. The present guidelines are intended to bundle the available knowledge about perioperative management of malignant hyperthermia-susceptible patients and the preparation of anaesthesia workstations. The latter aspect includes guidance on the use of activated charcoal filters. The guidelines were developed by members of the European Malignant Hyperthermia Group, and they are based on evaluation of the available literature and a formal consensus process. The most crucial recommendation is that malignant hyperthermia-susceptible patients should receive anaesthesia that is free of triggering agents. Providing that this can be achieved, other key recommendations include avoidance of prophylactic administration of dantrolene; that preoperative management, intraoperative monitoring, and care in the PACU are unaltered by malignant hyperthermia susceptibility; and that malignant hyperthermia patients may be anaesthetised in an outpatient setting.